Influence of different tool electrode materials on EDMed surface integrity of AISI P20 tool steel - Dewangan, S. (Taylor and Francis Inc., 2014)
Surface integrity in electro-discharge machining (EDM) has been proven to be one of the major challenges in recent years. The current study focused on investigating the influence of different tool electrode materials such as copper, brass, and graphite and various process parameters like discharge current (Ip), pulse-on time (Ton), duty cycle (Ï), and polarity on EDMed surface integrity. Since formation of white layer, surface cracks, and surface roughness (SR) predominantly influence surface integrity the same performance measures have been considered in the current study. The results indicated that maximum white layer thickness, surface crack density, and SR were obtained for graphite tool. Therefore, it cannot be recommended to use under the given operating condition. The brass tool performed best followed by copper tool when different aspects of surface integrity were analyzed. Pulse current was found to be the most influential process parameter affecting machined surface integrity of AISI P20 tool steel during EDM. Â© 2014 Taylor & Francis Group, LLC.